Mango (Mangifera indica L.) residue flour preparation for application in copper (II) removal in a water médium - Souza, Fernanda Kelly Alves de [UNESP]; Costa, Maria Laura Ferreira Della [UNESP]; Magdalena, Aroldo Geraldo [UNESP] (FapUNIFESP (SciELO), 2024)
Problem: The contamination of water bodies by copper (II) ions caused by industries harms the environment and human health. Solution: Adsorption removes such ions using activated carbon, which may be replaced with bioadsorbents (biomass from agro-industrial waste), as they are more accessible and renewable, capturing contaminant species from functional groups. This study verified the adsorption efficiency of copper (II) ions using mango residue flour (Mangifera indica L., MRF) as a bioadsorbent. Methodology: MRF preparation consisted of drying Tommy mango pits and seeds (80°C, 48 hours), crushing, sieving, and treating them with hydrochloric acid (0.05 mol L–1, 10 minutes). The MRF characterization techniques were FTIR and point of zero charge (PZC). Adsorption studies occurred at 25°C, pH of 4.6, and constant stirring. Adsorption time and MRF mass were the parameters to determine optimal adsorption conditions. Complexometric titration determined the concentration of adsorbed copper (II) ions. Results and discussion: FTIR identified the functional groups interacting with copper (II) ions. PZC determined that the surface charge of MRF is neutral at a pH of 4.3, positive and interacting with anions at a pH lower than 4.3, and negative and interacting with cations at a pH higher than 4.3. The optimal adsorption conditions were 30 minutes and 0.1 g of MRF. The non-linear Redlich-Peterson and Langmuir isotherm models provided the best fits, suggesting a multilayer MRF adsorption mechanism. The maximum percentage of copper (II) ion removal was 77.5%. Conclusion: Adsorption using MRF potentially removes copper (II) ions.
Keywords: Bioadsorption; Isotherms; Mangifera indica L; Metallic ions; PZC